Contributing Factors on Malaysia Preschool Teachers’ Belief, Attitude and Competence in Using Play Activities - Hafsah Binti Jantan; Abdul Rahim Bin Hamdan; Fauziah Hj Yahya; Halimatussadiah Binti Saleh (International Journal of Evaluation and Research in Education (IJERE), 2015)
This study focud on preschool teachers’ belief, attitude, knowledge and competence in using play in Malaysia. Its purpose is to find out indicators significantly contribute to belief, attitude, knowledge and competence in play of preschool teachers in Malaysia. The method used was factor analysis in order to confirm indicators in each variable as significant indicators as factors with loading factor 0.40. Sample size in this study consists of 150 respondents. The result showed belief has 3-factor solution namely content belief, language and literacy belief, and teaching belief. Attitude has 2-factor solution, namely emotion and behavior. Competence has 3-factor solution, namely implementation, content and guiding. Indicators of each factor were also discussed.